A Peek at the Tradeoff Relationship Between Expected Return and Risk - Summers, Robert (Quarterly Journal of Economics, 1967)
I. Introduction, 437. — II. A micro-model for analyzing a contingent remainder, 439. — III. Market aggregation, 446. — IV. Empirical analysis, 448. — V. Summary, 454. — Appendix, 455.